A Comparison of Buprenorphine + Naloxone to Buprenorphine and Methadone in the Treatment of Opioid Dependence during Pregnancy: Maternal and Neonatal Outcomes. (January 2013) - Lund, Ingunn O.; Fischer, Gabriele; Welle-Strand, Gabrielle K.; O'grady, Kevin E.; Debelak, Kimber; Morrone, William R.; Jones, Hendrέe E.
Given that buprenorphine + naloxone is prescribed for opioid-dependent pregnant women, it is important to examine the extent to which it differs from buprenorphine alone, methadone, or methadone-assisted withdrawal on neonatal and maternal outcomes. Summary statistics on maternal and neonatal outcomes were collected from 7 previously published studies examining treatment for opioid-dependent pregnant women that represented a range of research methodologies. Outcomes from these studies were compared to the same outcomes for 10 women treated with the combined buprenorphine + naloxone product. There were no significant differences in maternal outcomes for buprenorphine + naloxone compared to buprenorphine, methadone, or methadone-assisted withdrawal. Preliminary findings suggest no significant adverse maternal or neonatal outcomes related to the use of buprenorphine + naloxone for the treatment of opioid dependence during pregnancy. However, further research should examine possible differences between buprenorphine + naloxone and buprenorphine alone or methadone in fetal physical development.